New neotropical species of Trupanea (Diptera: Tephritidae) with unusual wing patterns - Norrbom, Allen L.; Neder, Lilia Estela (Zootaxa, 2014)
Four species of Trupanea Shrank (Diptera: Tephritidae) with unusual wing patterns are described from the Neotropical Region: T. dimorphica (Argentina), T. fasciata (Argentina), T. polita (Argentina and Bolivia), and T. trivittata (Argentina). Celidosphenella Hendel, 1914 and Melanotrypana Hering, 1944 are considered new synonyms of Trupanea, and the following species are transferred from Celidosphenella to Trupanea: Acinia bella Blanchard, 1852; Acanthiophilus benoisti Séguy, 1933; Tephritis diespasmena Schiner, 1868; Celidosphenella maculata Hendel, 1914; Sphenella poecila Schiner, 1868; Trypanea simulata Malloch, 1933; Trupanea stonei Stuardo, 1946; and Trypanea vidua Hering, 1942. Aphyllocladus spartioides Wedd. (Asteraceae: Mutisieae) is reported as a probable host plant for Trupanea dimorphica.